Role of Free Testosterone in Interpreting Physical Performance in Elite Young Brazilian Soccer Players - Moreira, A.; Mortatti, A.; Aoki, M.; Arruda, A.; Freitas, C.; Carling, C. (Pediatric Exercise Science, 2013)
This study investigated the contribution of salivary testosterone (sT) concentration, years from peak height velocity (YPHV) and height by body mass interaction on jumping performance (Countermovement jump; CMJ) and aerobic fitness (Yo-Yo intermittent endurance test, level 1) in young elite soccer players. Forty-five participants (age: 12.5 ± 0.5y; body mass: 48.6 ± 10.2kg, height: 155.7 ± 10.0cm) belonging to a top level Brazilian soccer club were evaluated at four time points across a single semester. None of the assessed players had reached PHV. The data from the four evaluations were averaged and multiple linear regression analysis conducted. For CMJ, the model explained 42.88% of the variance (R2 = 42.88; p < .000); sT concentration was the primary contributor (R2 = 32.84) and the YPHV contributed 9.95% of the variance. The model explained 28.50% (p < .000) of the variance in Yo-Yo. The sT was the primary and single significant contributor (R2 = 21.32). A significant difference was noted between high and low testosterone groups divided a posteriori to CMJ performance (t = 3.35; p = .001). These results suggest an important role for hormonal status in interpreting physical performance in preadolescent soccer players.